Why people use their cars while the built environment imposes cycling - Van Acker, Veronique; Derudder, Ben; Witlox, Frank (Journal of Transport and Land Use, 2013)
Residing in a high-density, diverse, and accessible neighborhood tends to be associated with less car use, more public transport, and more cycling and walking. However, this does not hold for all people because of differences in personal perceptions and preferences. This paper, therefore, analyzes spatial (mis)match, or the correspondence between perceptions of someone’s residence and the objectively measured spatial characteristics of that residence. Based on a sample for Flanders, Belgium, we found that people tend to overrate the urbanized character of their residence. Among urbanites, (mis)matched spatial perceptions do not influence mode choice. Mode choices remain mainly influenced by urban characteristics and not by personal perceptions as such. However, the influence of spatial (mis)match becomes more important among rural dwellers and, especially, suburbanites. The travel consequences of (mis)matched spatial perceptions thus clearly depend on the residential neighborhood type.